2019
DOI: 10.14309/01.ajg.0000594480.04971.10
|View full text |Cite
|
Sign up to set email alerts
|

1238 Tradipitant Complete Responder Analysis in Gastroparesis Patients

Abstract: INTRODUCTION: A Phase II multicenter, randomized, double-blind, placebo-controlled trial with gastroparesis subjects demonstrating delayed gastric emptying and moderate to severe nausea were randomized to receive oral 85 mg tradipitant bid or placebo (1:1) for four weeks. Of the 152 patients enrolled, 60% of patients had idiopathic and 40% had diabetic gastroparesis. METHODS: The primary outcome was change in average nausea score from baseline, measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent studies have demonstrated their efficacy in improving GCSI with a potential benefit in fundic accommodation. 80 , 81 …”
Section: Treatmentmentioning
confidence: 99%
“…Recent studies have demonstrated their efficacy in improving GCSI with a potential benefit in fundic accommodation. 80 , 81 …”
Section: Treatmentmentioning
confidence: 99%